Seed priming with potassium nitrate and gibberellic acid enhances the performance of dry direct seeded rice (Oryza sativa L.) in north-western India - Dhillon, Buta Singh; Kumar, Virender; Sagwal, Pardeep; Kaur, Navjyot; Singh Mangat, Gurjit; Singh, Sudhanshu (MDPI, 2021)
Poor early growth and uneven crop establishment are reported as the major bottlenecks in wide-scale adoption and optimal yield realization of dry direct-seeded rice (DSR). Seed priming can potentially help overcome these problems in DSR. Therefore, laboratory and field studies were conducted at Punjab Agricultural University, Ludhiana, India, during kharif/wet-season 2018 and 2019 to evaluate the effect of different priming techniques on germination, establishment, growth, and grain yield of rice under DSR conditions. The following priming treatments were evaluated: dry non-primed seed (control), hydropriming with distilled water, halopriming with 2.0% potassium nitrate, hormopriming with 50 ppm gibberellic acid (GA3), and osmopriming with polyethylene glycol (PEG)(−0.6 MPa), each with 12 and 24 h priming duration. In 2019, priming treatments were tested under two DSR establishment methods—conventional DSR (sowing in dry soil followed by irrigation) and soil mulch DSR (locally known as vattar DSR) (sowing in moist soil after pre-sowing irrigation), whereas in 2018, priming treatments were evaluated under conventional DSR only. In both years, halopriming and hormopriming resulted in a 7–11% increase in rice yields compared to non-primed dry seed (control). Osmopriming resulted in a 4% yield increase compared to control in 2018 but not in 2019. The higher yields in halopriming and hormopriming were attributed to higher and rapid germination/crop emergence, better root growth, and improvement in yield attributes. Priming effect on crop emergence, growth, and yield did not differ by DSR establishment methods and duration of priming. Conventional DSR and soil mulch DSR did not differ in grain yield, whereas they differed in crop emergence, growth, and yield attributes. These results suggest that halopriming with 2.0% potassium nitrate and hormopriming with 50 ppm GA3 has good potential to improve crop establishment and yield of rice in both conventional and soil mulch DSR systems.